Islamic Environmental Ethics in Global Context: A Trends, Gaps, and Theological Contributions - Adnan Nuril Anwar; Muh. Bahrul Afif; Anti Anfaul Lisani; Moch. Farich Alfani; Safinatul Umami (International Journal of Social Science and Religion (IJSSR), 2026)
This study shows that Islam’s contribution to the discourse on eco-theology and environmental ethics tends to be limited. In fact, Islam possesses a strong theological-ethical foundation through the concept of Islamic Environmental Ethics (IEE). Using the PRISMA method and VOSViewer software, the author conducted a search using the keywords “Islamic AND Environmental AND Ethics” and identified 265 articles from 2004 through May 31, 2026. After undergoing an inclusion and exclusion process, 30 relevant articles were selected for analysis. The results of the bibliometric analysis indicate that IEE studies have developed significantly, focusing on the themes of khalīfah, maslahah, and ‘adl (justice); however, the majority remain normatively and legalistically oriented without strengthening their theological foundations. Visual analysis indicates that IEE serves as a bridge between Islamic concepts and global environmental issues (responsibility, sustainability, and conservation). The author proposes the Ash‘ari theological framework as an alternative approach to reconstructing IEE into an integrative paradigm of ecological theology, while also opening space for interfaith dialogue in building a just and sustainable global environmental ethics.